Pengaruh Workplace Stretching-Exercise dan Edukasi Postur Kerja Angkat Angkut dengan Keluhan Low Back Pain pada Pengerajin Sepatu - Ellysa Okky Gusma; Indasah Indasah (FORIKES, 2022)
Fatigue can occur due to manual handling work, lifting and carrying activities that affect health problems or work accidents. One of the most common injuries is low back pain. So research is needed that aims to analyze the effect of giving workplace stretching and education on work postures on carrying and carrying work on complaints of low back pain in shoe craftsmen in Mojokerto. The design of this study was pretest-posttest with control group, which involved 66 shoe craftsmen in Mojokerto who had complaints of low back pain, then divided into two groups, each of 33 people. Measurement results data were analyzed using the Wilcoxon test and the Mann-Whitney test. Based on the Wilcoxon test, the experimental group showed better results with a value of p = 0.000, than the control group. Based on the Mann-Whitney test, it was found that the value of p = 0.000, so that it can be said that there is a difference between the two groups. Thus, there is an effect of giving workplace stretching-exercise and educating work postures on carrying and carrying complaints of low back pain.Keywords: lift-transport; work posture education; low back pain; shoe craftsman; workplace stretching ABSTRAK Kelelahan dapat terjadi akibat pekerjaan manual handling,kegiatan angkat-angkut beban mempengaruhi terjadinya gangguan kesehatan atau kecelakaan kerja. Salah satu cedera yang sering terjadi adalah low back pain. Maka diperlukan penelitian yang bertujuan untuk menganalisis pengaruh pemberian workplace stretching dan edukasi postur kerja angkat-angkut terhadap keluhan low back pain pada pengrajin sepatu di Mojokerto. Rancangan penelitian ini adalah Pretest-posttest with control group, yang melibatkan 66 pengrajin sepatu di Mojokerto yang memiliki keluhan low back pain, kemudian dibagi menjadi dua kelompok, masing-masing 33 orang. Data hasil pengukuran dianalisis menggunakan uji uji Wilcoxon dan uji Mann-Whitney. Berdasarkan uji Wilcoxon, kelompok eksperimen menunjukkan hasil lebih baik dengan nilai p = 0,000, daripada kelompok kontrol. Berdasarkan uji Mann-Whitney diperoleh hasil bahwa nilai p = 0,000, sehingga bisa dikatakan bahwa terdapat perbedaan antara kedua kelompok. Dengan demikian, ada pengaruh pemberian workplace stretching-exercise dan edukasi postur kerja angkat-angkut terhadap dengan keluhan low back pain.Kata kunci: angkat-angkut; edukasi postur kerja; low back pain; pengrajin sepatu; workplace stretching